Brain responses to emotional infant faces in new mothers and nulliparous women - Zhang, Kaihua (2020)
The experience of motherhood is one of the most salient events in a woman's life. Motherhood is associated with a series of neurophysiological, psychological, and behavioral changes that allow women to better adapt to their new role as mothers. Infants communicate their needs and physiological states mainly through salient emotional expressions, and maternal responses to infant signals are critical for infant survival and development. In this study, we investigated the whole brain functional response to emotional infant faces in 20 new mothers and 22 nulliparous women during functional magnetic resonance imaging scans. New mothers showed higher brain activation in regions involved in infant facial expression processing and empathic and mentalizing networks than nulliparous women. Furthermore, magnitudes of the activation of the left parahippocampal gyrus and the left fusiform gyrus, recruited during facial expression processing, were positively correlated with empathic concern (EC) scores in new mothers when viewing emotional (happy-sad) faces contrasted to neutral faces. Taken together, these results indicate that the experience of being a mother affects human brain responses in visual and social cognitive brain areas and in brain areas associated with theory-of-mind related and empathic processing.